Aplicação da microtomografia de raios X no processo de caracterização das estruturas internas do concreto - Bastos, Luan Ferreira (2019)
X-ray microtomography is a non-destructive method that allows the visualization of the internal structure of the object and makes possible to generate trust internal graphics models of the object. Concrete is a mixture widely used in the construction industry due to the union between its mechanical properties with the low cost for its production. The application of X-ray microtomography in concrete structures allows the visualization of the layout and formation of existing internal structures in the concrete. The work presents a methodology to segment, quantify and analyze the structures of pores, the high densities aggregates and fibers, which were classified according to ASTM C125-18 and NBR 7211:2009. After the classification, was noticed the predominance of aggregates with a lower degree of fineness and the majority of pores with the volume between 0.0001 and 0.01 mm³. It was also possible to identify the presence of EVA and piaçava fibers in the internal structure of the samples, which are lightweight concrete. X-ray microtomography system showed its efficiency in the study of the internal structures of the concrete.